Labor Supply of Mothers: The Role of Time Discounting - Peter Haan; Luke Haywood; Ulrich Schneider (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
We estimate a dynamic life-cycle model of labor supply with a focus on time preferences for women. We extend the dynamic discrete choice model to accommodate potentially non-exponential discounting. Variation in job protection regulations provides identifying variation to test time discounting, affecting future and not current payoffs. Reforms to job protection legislation in Germany constitute a natural experiment to identify the key time preference parameters of our model. We shed light on the importance of time-inconsistent preferences on maternal labor market return. The structure of time preferences will importantly affect cost and effectiveness of labor market policies.
Keywords: J24; D91; E24; 330